Argumentative Processes among Chilean Teachers Regarding their Collaborative experience as part of the Universal Design for Learning Framework - Moreno Díaz, Karina del Carmen (2021)
The Universal Design for Learning [UDL] is a series of guidelines that serve as a framework to develop more varied and engaging learning opportunities for students.  Chile adopted the UDL after passing Decree 83. Implementation of UDL requires strong collaboration among educators. The objective of this study was to understand teacher collaboration within the UDS based on their reflections. A qualitative research method based on a series of interviews was conducted among twelve primary school teachers. The interviews were divided into two stages - argumentative and episodic - to represent the complexity of the reflections. Responses were analysed based on a grounded theory approach. According to the results, teachers acknowledged that any collaborative effort aimed at diversifying teaching was conditioned by institutional factors. Furthermore, successful collaborative experiences are characterized by interdependence, mutual recognition, and trust. Positive results about student motivation and student development are included. Teacher reflection reveals that when diversification is worked together with cooperative learning. These results are discussed at an institutional, professional relationship and classroom level, concluding that each element thoughtfully addressed by teachers is relevant and forms an articulated structure. The main implications include: understanding the implementation of the UDL as a joint reflective process, creating the cultural, relational, training, time and educational policy-related conditions and performing UDL in the classroom using cooperative learning structures.